Parental views on money management - Galera, Renee Lyn Garrido; Palacpac Jr., Orlino (2007)
Parents play an important role in developing their children's financial literacy. Parents use various media and approaches in teaching children to manage money. It is assumed that parental views regarding money and money management could serve as the basis for instruction. This qualitative study sought to examine parental strategies in introducing money management knowledge and skills to their children. The research also aimed to explore on principles behind parental money management. To accomplish this, sample size of thirty parents was determined at 90% confidence level and ±15% confidence interval. The questionnaires were administered in three selected subdivisions in Caloocan City. The instrument was designed to explore parental perspectives on: money and money management principles; important uses of money; implementation of money management skills; schedule of giving money to a child; and media for teaching money and money management. Data gathered was analyzed using content analysis. Results of the study indicated that money management training starts when parents hand over money as allowance. This is usually initiated to children as early as four years old. Most respondents give twenty pesos as daily allowance. Respondents also declared that money is important to purchase basic family necessities. Parents emphasized that saving money should be the first lesson learned by children.
Thesis (BS Home Economics)--University of the Philippines Diliman.
Keywords: Finance, Personal